Analisis Penerapan Teknologi dan Best Management Practice Budidaya Udang Vanname (Litopenaeus Vannamei) di Tambak Kecamatan Mananggu - Nur Awalia; Hasim; Sutianto Pratama Suherman (Transbahasa, 2024)
Vannamei shrimp farming requires the proper application of technology and management to enhance productivity and sustainability. This study aims to analyze the application of the best technology and management practices by vannamei shrimp (Litopenaeus vannamei) farmers in Mananggu District, Boalemo Regency, Gorontalo Province. The methods used include observation and interviews with 8 out of 11 farmers, with data collected through questionnaires focusing on six indicators of Best Management Practices (BMP): pond preparation, feed management, seed management, water quality management, pest and disease monitoring, and harvesting. The results show that 7 out of 8 farmers implemented technology during the pond preparation stage. Education level also influenced practices, with 62.5% of respondents having higher education (high school to bachelor's degree). The application of BMP plays a crucial role in improving the efficiency of vannamei shrimp farming in this area.